Determinants of energy intake in Central African populations experiencing nutrition transition - (:unkn) unknown (My University, 2022)
Abstract Central Africa is experiencing rapid urbanisation, and this situation comes along with changes in food habits and an increased prevalence of obesity and associated health risks. Factors influencing dietary intake among the diverse African populations are not well understood. Our objective was to characterise the dietary intake and their determinants in the two main ethnic groups experiencing nutrition transition in Cameroon, the Bamiléké and the Béti. We sampled Bamiléké (381) and Béti (347) adults living in both rural and urban, collected socio-demographic variables, assessed dietary patterns by using a food portion photographs book to administrate a FFQ and a 24-h dietary recall technique and derived their BMI from measured weight and height. The dietary patterns of Bamiléké people were composed of more energy-dense foods than the Béti people, regardless of the living area. The energy intake (13·8 ( sd 4·6)–15·4 ( sd 4·8) MJ v . 9·7 ( sd 3·5)–11·2 ( sd 3·9 MJ) and the obesity (15–29 % v . 5–8 %) were therefore higher in Bamiléké than in Béti, respectively. Multivariable linear regression analyses showed strong associations of both ethnicities (4·02 MJ; P < 0·001), living area (0·21 MJ; P < 0·001) and education (0·59 MJ; P < 0·048) with energy intake, independently of each other and other socio-demographic factors. The ethnicity factor has been characterised as the more important determinant of diet. Our findings provide new insights and perspectives highlighting the importance of anthropological factors when building prevention campaigns against obesity in Central Africa.
Keywords: African Research